The influence of internship experience, career guidance, and vocational interests on students' work readiness - Dora Papince; Kasmita Kasmita; Giatman Giatman; Ari Syaiful Rahman Arifin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the relationship between industrial work practice experience, career guidance, and vocational interest and students’ work readiness at SMK Negeri 1 Sutera. Work readiness was operationalized as a multidimensional construct including technical competence, work attitude, and adaptability. A quantitative correlational design was employed with a sample of 130 students selected using proportional random sampling. Data were collected through validated questionnaires adapted from previous studies, with acceptable validity (r > 0.30) and reliability (Cronbach’s alpha > 0.70). Data were analyzed using multiple regression after meeting assumptions of normality, linearity, and multicollinearity. The results show that vocational interest has the strongest association with work readiness (β = 0.606, p < 0.001), followed by industrial work practice (β = 0.418, p < 0.001) and career guidance (β = 0.363, p < 0.01). Simultaneously, the three variables explain 31.4% of the variance in work readiness. These findings suggest that both experiential learning and intrinsic motivation are important factors, although other variables beyond this model also contribute to students’ work readiness.